Obserwator Wielkopolski . pismo członków i sympatyków NSZZ "Solidarność", no. 117, 1988 - NSZZ "Solidarność", [ed. Jan Krzysztof Adamkiewicz, Michał Dziurla, Grzegorz Gauden] (NSZZ "Solidarność", 1988)
Creation and circulation: For organizational use. Issues no. 1-27(1981) and from issue no. 1(4 III 1990) published legally. From issue no. 1(1982) to no. 136(1990) published underground.